2023
DOI: 10.2147/iprp.s416830
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dispensing Malpractice in Community Drug Retail Outlets in South Gondar Zone, Northwest Ethiopia: A Simulated Patient Experience

Abstract: Background Pharmacy professionals in community drug retail outlets, as the most accessible personnel for the community, are engaged in consultation and responding to health problems in addition to filling prescriptions. In doing so, different dispensing malpractices are observed and much is not known on the issue in Ethiopia. Objective The study aimed at assessing dispensing malpractice at pharmacies, drug stores and drug vendors in South Gondar zone. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…While 89.02% of respondents ( 14 ) said it was a lack of sufficient information that caused the negative consequences, 38.8% of respondents ( 15 ) also believed it was. In Gondar city, studies have revealed that self-medication practices and easy access to prescription medicines have increased significantly in recent years ( 16 , 17 ). Consequently, medicines may go unused or become outdated and expired and are disposed of indiscriminately.…”
Section: Introductionmentioning
confidence: 99%
“…While 89.02% of respondents ( 14 ) said it was a lack of sufficient information that caused the negative consequences, 38.8% of respondents ( 15 ) also believed it was. In Gondar city, studies have revealed that self-medication practices and easy access to prescription medicines have increased significantly in recent years ( 16 , 17 ). Consequently, medicines may go unused or become outdated and expired and are disposed of indiscriminately.…”
Section: Introductionmentioning
confidence: 99%